2013
DOI: 10.1002/aic.14293
|View full text |Cite
|
Sign up to set email alerts
|

Bubble point pressures of binary methanol/water mixtures in fine‐mesh screens

Abstract: Binary methanol/water mixture bubble point tests involving three samples of fine-mesh, stainless steel screens as porous liquid acquisition devices are presented in this article. Contact angles are measured as a function of methanol mass fraction using the Sessile Drop technique. Pretest predictions are based on a Langmuir isotherm fit. Predictions and data match for methanol mole fractions greater than 50% when pore diameters are based on pure liquid tests. For all three screens, bubble point is shown to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The second finest 450x2750 mesh produced the highest bubble points, for both GHe and GH 2 . The 510x3600 mesh outperformed the 325x2300 mesh at LH 2 temperatures, but the 325x2300 yielded higher pressures in room temperature liquids [11,12]. The reason for this crossover in performance is due to the temperature dependence of the screen pore diameter, as mentioned previously.…”
Section: Liquid Hydrogen Testsmentioning
confidence: 73%
See 2 more Smart Citations
“…The second finest 450x2750 mesh produced the highest bubble points, for both GHe and GH 2 . The 510x3600 mesh outperformed the 325x2300 mesh at LH 2 temperatures, but the 325x2300 yielded higher pressures in room temperature liquids [11,12]. The reason for this crossover in performance is due to the temperature dependence of the screen pore diameter, as mentioned previously.…”
Section: Liquid Hydrogen Testsmentioning
confidence: 73%
“…The bubble point is defined as the differential pressure across a LAD screen pore that overcomes the surface tension forces at that pore. Bubble point pressure is proportional to the surface tension of the liquid and inversely proportional to the effective screen pore diameter, as derived in Hartwig and Mann [11,12] and shown in Eq. 1:…”
Section: The Bubble Point Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…The bubble point is defined as the differential pressure across a LAD screen pore that overcomes the surface tension forces at that pore. Bubble point pressure, P BP , is proportional to the surface tension of the liquid and inversely proportional to the effective screen pore diameter, as derived in [11,12] and shown in Equation 1:…”
Section: The Bubble Point Pressurementioning
confidence: 99%
“…Based on previously reported cryogenic bubble points from McQuillen (2011 and2012a), the model is only valid for normally saturated liquids. Hartwig and Mann (2013b) showed that Equation (1) simplifies to…”
Section: The Bubble Pointmentioning
confidence: 99%